Calm Weathers: Barthes with Beckett. Issue 2 (July 2022) - Leca, Diana
Abstract : Calm is a little-theorized but important link between Roland Barthes and Samuel Beckett. Beginning with Beckett, moving on to Barthes, and then interleaving the two, this paper proposes calm as a 'scandalous' category not reducible to kindred states like languor or apatheia . In dialogue with theorists of repose, such as Kant and De Quincey, calmness becomes less a sedated condition than an interactive process, entailing intense sensitivity to the fluctuations of what Barthes calls 'the affective minimal'. Artistically generative, this 'emotive lucidity' encourages inquisitiveness towards the natural world, and enables in both writers specific writing practices — from lists to notation to haiku.